2018
DOI: 10.1536/ihj.17-446
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Transcription Factor C/EBPβ Plays a Critical Role in Cardiac Fibroblast Differentiation and a Rat Model of Cardiac Fibrosis Induced by Autoimmune Myocarditis

Abstract: The aim of the present study was to investigate the mechanisms of CCAAT/enhancer-binding protein β (C/ EBPβ) in cardiac myofibroblast (CMF) differentiation and in a rat model of cardiac fibrosis induced by experimental autoimmune myocarditis (EAM). In vitro studies performed in primary neonatal rat CMF revealed that silencing of C/EBPβ expression (via lentiviral mediated shRNA strategies) was sufficient to reduce C/EBPβ mRNA and protein levels as well as to decrease the expressions of actin cytoskeletal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Thus, the cytoskeleton undergoes intense remodelling during this process. The role of the cytoskeletal system, including cofilin, fascin, profilin 1 and other cytoskeletal binding proteins, in autoimmune diseases has been reported 9,10 . In our previous study, we found that the expression of profilin 1 increases on the mDCs of patients with SAA, and this may affect mDC function 17 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Thus, the cytoskeleton undergoes intense remodelling during this process. The role of the cytoskeletal system, including cofilin, fascin, profilin 1 and other cytoskeletal binding proteins, in autoimmune diseases has been reported 9,10 . In our previous study, we found that the expression of profilin 1 increases on the mDCs of patients with SAA, and this may affect mDC function 17 .…”
Section: Discussionmentioning
confidence: 81%
“…The role of the cytoskeletal system, including cofilin, fascin, profilin 1 and other cytoskeletal binding proteins, in autoimmune diseases has been reported. 9 , 10 In our previous study, we found that the expression of profilin 1 increases on the mDCs of patients with SAA, and this may affect mDC function. 17 In the present study, we observed that the expression of cofilin‐1 in mDCs from patients with SAA increased at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For instance, protein levels of C/EBP α decrease in carbon tetrachloride- (CCl 4 -) induced fibrotic liver tissue, and overexpression of C/EBP α in the liver can alleviate CCl 4 -induced hepatic fibrosis [ 28 , 37 ]. C/EBP β expression is inhibited in diabetic cardiomyopathy- (DCM-) induced fibrotic heart tissue, and overexpression of C/EBP β inhibits this cardiac fibrosis, while C/EBP β knockdown attenuates heart fibrotic pathology in rat models of experimental autoimmune myocarditis (EAM) [ 34 , 38 ]. The overactivation of C/EBP γ induced by IL-1 β inhibits IL-6 expression in lung epithelial cells, which indirectly suppresses lung fibrosis [ 25 , 39 ].…”
Section: Introductionmentioning
confidence: 99%